Protection of Globally Renowned Brands Which Not Registered in Indonesia - Daniella Natasha; Shelvi Rusdiana (Amnesti Jurnal Hukum, 2023)
The protection arrangements for unregistered globally well-known brands are not explained in detail regarding their protection from passing off in Indonesia. This study aims to analyze how the protection of well-known marks that have not been registered in Indonesia and to prove that internationally registered marks that have not been registered in Indonesia must still be protected in Indonesia. This research is legal research that uses normative juridical research methods by emphasizing argumentation and uncovering meaning by interpreting existing laws and regulations based on the legal system relating to trademark protection. The results of the research show that Article 83 (2) of Law No. 20 of 2016 concerning Trademarks and Geographical Indications (hereinafter referred to as the MIG Law) does not protect brand indications other than the indications regulated in Article 1 paragraph (1) of the MIG Law. Furthermore, with the argument that a lawsuit can only be filed after the lawsuit for cancellation has started indicates that Article 83 (2) only covers violations of the transfer of well-known marks that are not registered through third-party registration. Meanwhile, the violation of passing off by using an unregistered name without legal rights is not covered in this article. In addition, the enactment of Article 83 (2) does not fully accommodate passing off lawsuits in Indonesia.